A colourful death [large type] - Dunn, Carola (Dunn, Carola. Cornish mysteries., 2010)
Recently retired widow Eleanor Trewynn has moved to the small Cornwall village of Port Mabyn, ready for an uneventful life with her dog and her friends. Unfortunately, excitement seems to happen around her. Her friend and neighbor, Nick Gresham, returns from a trip to find his paintings slashed, reportedly by rival local artist Geoffrey Clarke. When Nick goes to have it out with him, with Eleanor in tow, they find Clarke's body, fatally stabbed in the back.